Kegiatan Sosialisasi Pelatihan Pajak Dan Konsultasi Pajak Pada Pemuda Muhamadiyah Ranting Rowosari Ulujami - Muhammad Isa Anshory; Wahid Wahyu Adi Winarto; Bahtiar Effendi (Madani : Indonesian Journal of Civil Society, 2023)
Community service activities for the Muhammadiyah Youth branch of Rowosari Ulujami branch which is one of the activities of the Tri Dharma of Higher Education aims to increase understanding and add to the scientific repertoire of taxation in accordance with tax regulations as a provision to become a good taxpayer and can contribute to the country's successful development . Using the community service method through several activities and stages to carry out tax training socialization activities and tax consultations. In this activity, about 50 participants participated in the Mummadiyah youth from the Rowosari Ulujami branch and participated with high enthusiasm because they wanted to learn about taxation because Muhammadiyah Youth had limited knowledge about taxes so that this service activity could transfer knowledge of taxation to the participants. From the results of the initial test and the final test that had been carried out, unique results were obtained, namely from the pre-test, post-test which were attended by approximately 50 participants, the value of 25.8 with the predicate changed very little to 88.74 with a good predicate.